ESG PRACTICES AND SIMPLE AI ADOPTION IN ISLAMIC-VALUE-BASED MSMES - Sari, Rafika Meilia; Puspitasari, Ayu Febri; Mashudi, Mashudi; Umayah, Galuh Siti Dewi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study investigates the role of simple Artificial Intelligence (AI) adoption, Environmental, Social, and Governance (ESG) practices, and Islamic value internalization in enhancing the sustainability performance of Micro, Small, and Medium Enterprises (MSMEs) in Tulungagung Regency, Indonesia. Using a quantitative explanatory research design, data were collected from 96 MSME owners or managers through structured questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all three variables have a positive and significant effect on sustainability performance, with ESG practices exerting the strongest influence. Simple AI adoption improves operational efficiency, decision-making transparency, and governance compliance, while Islamic values reinforce ethical conduct and stakeholder trust. Moreover, ESG practices mediate the relationship between AI adoption and sustainability performance, indicating that technological tools can effectively drive sustainable outcomes when aligned with ESG principles. This research contributes theoretically by integrating ESG, Islamic ethics, and technology adoption in the MSME context a combination rarely examined in prior studies. Practically, the study offers strategic guidance for policymakers, Islamic financial institutions, and MSME actors to promote ethical, technology-enabled, and sustainability-oriented business models. The results also align with the Sustainable Development Goals, particularly Goals 8, 9, and 12, supporting Indonesia’s commitment to inclusive and responsible economic growth.